INSIGHTS INTO THE MOLECULAR AND BIOCHEMICAL ROLE OF QUINIC ACID IN ALLEVIATING ETHANOL-INDUCED LIVER TOXICITY IN A RAT MODEL: EXPLORING OXIDATIVE STRESS, INFLAMMATION, AND APOPTOSIS SIGNALING PATHWAYS - GURUSAMY MUTHUKARUPPIAH,; NADANAM SARAVANAN, (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: The study aimed to evaluate the effects of quinic acid, a natural bioactive compound, on tissue and circulatory antioxidant status, lipid peroxidation, and its anti-apoptotic and anti-inflammatory mechanisms in ethanol-induced hepatotoxicity in rats. Methods: The rats were divided into four groups. Groups 1 and 4 were administered isocaloric glucose. Groups 2 and 3 received 30% ethanol at a dose of 5 g/kg body weight daily. In addition, Groups 3 and 4 were treated with quinic acid (50 mg/kg body weight) dissolved in 2% dimethyl sulfoxide. Results: The results demonstrated significantly elevated levels of tissue thiobarbituric acid reactive substances (TBARS), conjugated dienes (CD), and lipid hydroperoxides (LOOH), along with significantly reduced enzymatic and non-enzymatic antioxidant activities, including superoxide dismutase (SOD), catalase (CAT), and glutathione-related enzymes such as glutathione peroxidase (GPx), glutathione reductase (GR), and glutathione-S-transferase (GST), as well as reduced levels of glutathione (GSH), Vitamin C, and Vitamin E in ethanol-treated rats compared to the control group. Administration of quinic acid to rats with ethanol-induced liver injury significantly reduced the levels of TBARS, LOOH, and CD while markedly increasing the activity of SOD, CAT, GPx, GR, GST, and levels of GSH, Vitamin C, and Vitamin E in liver tissues compared to untreated ethanol-exposed rats. In addition, ethanol-treated rats showed increased mast cell accumulation, which was reduced by quinic acid treatment, along with elevated expressions of inflammatory and apoptotic markers, including Bax, Caspase-9, tumor necrosis factor-alpha, Nuclear factor kappa B, and interleukin-6, and a decreased expression of Bcl2 in the liver. Quinic acid supplementation in ethanol-fed rats reversed these ethanol-induced changes. Immunohistochemical studies further supported these findings. Conclusion: Quinic acid, with its antioxidant, anti-inflammatory, and anti-apoptotic properties, may offer a therapeutic option for protecting against ethanol-induced hepatotoxicity